Respuesta :

Hi,

Let's solve the equation step by step.

6(a+3)=18+6a

Step 1: Simplify both sides of the equation.

6(a+3)=18+6a

(6)(a)+(6)(3)=18+6a(Distribute)

6a+18=18+6a

6a+18=6a+18

Step 2: Subtract 6a from both sides.

6a+18−6a=6a+18−6a

18=18

Step 3: Subtract 18 from both sides.

18−18=18−18

0=0

Answer:

All real numbers are solutions.

Have a great day!

6(a+3)=18+6a    (distribute the 6)

6a+18=18+6a    (subtract 18 to both sides)

6a=6a    (divide 6 to both sides)

a=a    

When it's like this, you can see that whatever "a" value you plug in, it'll make the equation true. This means that a=infinitely many solutions

ACCESS MORE